GAMBARAN PROSEDUR PENYIMPANAN BAHAN MAKANAN KERING DI INSTALASI GIZI RUMAH SAKIT UMUM DAERAH PROVINSI NUSA TENGGARA BARAT - Romi Hidayatullah; Muhammad Habibullah Aminy; Slamet Mardiyanto Rahayu; Lale Ajeng Khalifatun Wardani; Wahyu Aprilyaningsih (Nusadaya Journal of Multidiciplinary Studies, 2025)
This study aimed to describe the procedures for storing dry food ingredients at the Nutrition Installation of Rumah Sakit Umum Daerah Provinsi Nusa Tenggara Barat. A descriptive approach was employed, involving direct observation of storage practices, arrangement of materials, temperature and humidity control, and compliance with dry food specifications. The results indicated that the storage requirements for dry food ingredients were met at 90.9%, while the types of dry food stored fully complied with the specifications at 100%. These findings demonstrate that the nutrition installation has implemented proper storage procedures in accordance with established standards, thereby ensuring the quality and safety of food provided to patients.